2012
DOI: 10.4103/2230-8229.94003
|View full text |Cite
|
Sign up to set email alerts
|

The major medical ethical challenges facing the public and healthcare providers in Saudi Arabia

Abstract: Background:Despite the relatively high expenditure on healthcare in Saudi Arabia, its health system remains highly centralized in the main cities with its primary focus on secondary and tertiary care rather than primary care. This has led to numerous ethical challenges for the healthcare providers. This article reports the results of a study conducted with a panel of practitioners, and non-clinicians, in Saudi Arabia, in order to identify the top ten ethical challenges for healthcare providers, patients, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 8 publications
2
42
0
Order By: Relevance
“…Issues dealing with confidentiality, discharge against medical advice (DAMA), religion and culture, and informed consent were the most recognized by the respondents, while their knowledge about just allocation of resources, conflict of interest, and end of life matters was poor. In a study carried out among public and private healthcare practitioners in Saudi Arabia, patient rights, equity of resources (just allocation of resources), confidentiality, and patient safety were the top four dilemma encountered by respondents 18. It could be deduced from the above that the lack of knowledge of the principles of biomedical ethics correlates to a significant extent with the identification or otherwise of ethical dilemmas in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Issues dealing with confidentiality, discharge against medical advice (DAMA), religion and culture, and informed consent were the most recognized by the respondents, while their knowledge about just allocation of resources, conflict of interest, and end of life matters was poor. In a study carried out among public and private healthcare practitioners in Saudi Arabia, patient rights, equity of resources (just allocation of resources), confidentiality, and patient safety were the top four dilemma encountered by respondents 18. It could be deduced from the above that the lack of knowledge of the principles of biomedical ethics correlates to a significant extent with the identification or otherwise of ethical dilemmas in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…15 A number of studies have discussed cultural nuances in individual nations. For example, Alkabba and colleagues 16 reported the challenge of accepting confidentiality and informed consent as major components of professionalism in Saudi Arabia. In Pakistan, Humayun et al 17 found that there was a striking lack of awareness of these principles, potentially due to the paternalistic model of patient care in many Asian cultures.…”
mentioning
confidence: 99%
“…Comparing our results (which concluded that the top three were disagreement among patients/family and healthcare professionals, treating patients with impaired or uncertain decision-making, and conflict with the administration policy) with the only local study done by Alkabba et al [10], which showed the top three ethical issues were patients' rights, equity of resources, and patients' confidentiality. Disagreement among patients/family and healthcare professionals about treatment decisions, handling end-of-life issues or DNR decisions, and disclosing the diagnosis were commonly reported ethical issues in other countries as well [3,6,9].…”
Section: Discussionmentioning
confidence: 47%
“…The advantage of this study is addressing the real and common ethical issues faced in daily practice by physicians. Although these challenges have been addressed in the literature as isolated ethical issues in healthcare, no attempt has ever been made to collate and prioritize them in our community [10][11][12][15][16][17][18][19][20][21][22][23][24]. This study encompasses a different spectrum of physicians regarding gender, different subspecialties, training level, and whether they practiced in private or government hospitals.…”
Section: Discussionmentioning
confidence: 99%